Assessment of pembrolizumab exposure in different patient subpopulations using pharmacometric simulation - Homšek, Ana; Jovanović, Marija; Miljković, Branislava; Vučićević, Katarina (Archives of Pharmacy, 2022)
Monoclonal antibodies’ pharmacokinetics is, due to their specific properties, highly variable among different patients. Beside body weight and albumin levels, pembrolizumab pharmacokinetics may also be affected by patient’s condition depicted as ECOG (Eastern Cooperative Oncology Group) performance status and tumor burden. The study aim was to compare pembrolizumab exposure in different patient subpopulations after administration of fixed (200 mg) and weight-based dosing regimen (2 mg/kg) every three weeks. Two virtual populations were generated in the R software: normal body weight patients with preserved renal function, normal albumin levels (3.4-5.8 g/dL) and good prognosis (ECOG 0, low burden); and underweight patients with decreased renal function, hypoalbuminemia (<3.4 g/dL) and poor prognosis (ECOG 1, high burden). The simulation was performed using an already developed two-compartment covariate model. Drug exposure is expected to be higher in the underweight group after the fixed dose administration compared to normal patients. As for weight-based administration, equivalent drug exposure was observed in both groups, as reduced clearance in the underweight group leads to similar drug concentrations. In the group of normal patients, no significant difference was observed between the two proposed dosing methods. Based on the conducted simulation, it is expected that all patients, regardless of the dosing method, will have exposures to pembrolizumab that provide effective treatment. Since the use of a fixed dose is more cost-effective, and increased pembrolizumab exposure in underweight patients with poor prognosis could lead to adverse reactions, therapeutic-drug-monitoring-based dosing should be considered in such patients.